THE TENDENCY TOWARD A CONNECTION BETWEEN THE FUNCTION AND TYPE OF LAND PARCELS AND BUILDINGS Case Study: The Western Part of Bandung - Clarissa Tanuwijaya (Riset Arsitektur (RISA), 2017)
Abstract- The expansion of the western part of Bandung was preceded by one of the main roads named Groote Postweg (Jalan Jendral Sudirman). Apart from this road, the area was developed further with the expansion of buildings on Jalan Layang Cimindi in an effort to curb traffic congestion, along with a railway route and vertical buildings that left their mark on the architecture of Bandung.The development of the area emerged through the presence of a variety of functions that affected the types and variants of land parcels (kaveling) and buildings in this part of town. The relevant data were obtained by reduplicating maps of the area dating back to 996, 2003, 2007, 2010, and 2015. The area’s expansion is discussed in synchronic and diachronic ways showing the local sitauation from 1996 to 2015. This part of West Bandung starts from Jalan Jendral Sudirman (at the Jalan Jamika three-way intersection) reaching Jalan Raya Cibeureum (until the Pasteur Tollroad). This expansion has been based on the variety of land parcels and the range of building types that have emerged over the years, resulting in the tendency toward a range of functions, types of land parcels and diversity of buildings. This trend is based on the outcome of a field survey, and the data have been obtained by way of the Statistical Package for the Social Sciences (SPSS). The buildings show a tendency toward certain dominant functions, that is to say being mainly commercial in nature, two-storied in addition to single buildings and small types of land parcels. Less dominant functions have also affected the skyline and urban lay-out or planning, in the shape of the Sudirman Suite Apartments whose height amounts to no fewer than 20 stories.Keywords: urban architecture development, range of functions, range of land parcels, variety of building types, tendency